2022
DOI: 10.1016/j.jbc.2021.101457
|View full text |Cite
|
Sign up to set email alerts
|

The two paralogous copies of the YoeB–YefM toxin–antitoxin module in Staphylococcus aureus differ in DNA binding and recognition patterns

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Our previous study demonstrated that the establishment of protein–DNA interaction might be associated with the recognition of both core and flanking sequences in the promoter DNA fragments [ 21 , 22 ]. To assess whether flanking sequences are critical to Ino2p DBD /Ino4p DBD /DNA mutual interaction, nucleotides corresponding to the flanking promoter DNA sequence were mutated (see Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study demonstrated that the establishment of protein–DNA interaction might be associated with the recognition of both core and flanking sequences in the promoter DNA fragments [ 21 , 22 ]. To assess whether flanking sequences are critical to Ino2p DBD /Ino4p DBD /DNA mutual interaction, nucleotides corresponding to the flanking promoter DNA sequence were mutated (see Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, these results suggest that residues (Ino2p His12/Glu16/Arg20/Arg44 and Ino4p His12/Glu16/Arg20 ) are critical for the optimal DNA binding affinity of the Ino2p DBD -Ino4p DBD heterodimer complex. Our previous study demonstrated that the establishment of protein-DNA interaction might be associated with the recognition of both core and flanking sequences in the promoter DNA fragments [21,22]. To assess whether flanking sequences are critical to Ino2p DBD /Ino4p DBD /DNA mutual interaction, nucleotides corresponding to the flanking promoter DNA sequence were mutated (see Figure 5A).…”
Section: Structural Basis For the Recognition And Binding Of Promoter...mentioning
confidence: 99%
See 1 more Smart Citation
“…Toxin–antitoxin modules were initially identified as a plasmid stability factor in the conjugative plasmids in the 1980s ( Ogura and Hiraga, 1983 ; Jaffe et al, 1985 ; Gerdes et al, 1986 ; Cooper and Heinemann, 2000 ; Van Melderen, 2010 ; Ni et al, 2021 ). Later, they turned out to be widely distributed on the chromosomes and mobile genetic elements (MGEs) in bacteria, archaea, and bacteriophage, especially pathogenic bacteria ( Ogura and Hiraga, 1983 ; Hayes and Van Melderen, 2011 ; Fraikin et al, 2020 ; Leroux et al, 2020 ; Kamruzzaman et al, 2021 ; Ni et al, 2021 ; Xue et al, 2022 ). It is worth noting that MGE is closely related to the genetic stability and formation of persisters through horizontal transfer and vertical transmission ( Cooper and Heinemann, 2000 ; Costa et al, 2001 ; Schumacher et al, 2012 , 2015 ; Blair et al, 2015 ; Levin-Reisman et al, 2017 ; Ni et al, 2021 ; Xia et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Followed by the degradation of the corresponding antitoxin partner, the active toxin component was, thus, released to interact with cellular pathways to activate potentially deleterious toxic activities ( Muthuramalingam et al, 2016 ; Leroux et al, 2020 ; Sarpong and Murphy, 2021 ; Xia et al, 2021 ). Furthermore, the type II TAS, which is studied the most and best, is the most abundant in bacterial MGEs among eight TAS types investigated to date ( Xie et al, 2018 ; Kamruzzaman et al, 2021 ; Sarpong and Murphy, 2021 ; Zhang et al, 2021 ; Xue et al, 2022 ). For instance, Ep RatAB and Ep YefM-YoeB TAS from Edwardsiella piscicida are thought to be the model organism for the study of intracellular infections and refer to antibiotic resistance and host infection ( Ma et al, 2021 ; Du et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%